Pengaruh Keselamatan dan Kesehatan Kerja (K3) terhadap Kinerja Karyawan PT Pupuk Sriwijaya Palembang Bagian Utilitas IB - Aldani, Dhiya Shofi; Andriana, Isni; Siregar, Lina Dameria (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of Occupational Health and Safety to the employee’s performance at PT. Pupuk Sriwijaya Palembang Utility Division IB which amounts to 52 employees. This study used saturated sampling techniques. The data used in this study is primary data with data collection technique used is through questionnaires. The data analysis technique used is sample linear regression analysis. Based on the results of the study showed that the occupational health and safety had a positive and significant effect on employee performance at PT. Pupuk Sriwijaya Palembang Utility Division IB. Keywords: Occupational Health and Safety, Employee Performance